Simulation analysis of the wild animal observation system. (29th October 2020) - Hui, Lin; Wang, Kuei Min; Chen, Yung-Hui; Hung, Fu-Yi
The Chinese white dolphin, along the west coast of Taiwan, is claimed as on the brink of distinction species. A top priority before entering the policy process of conservation is to have a well plan of accurate observation. Objective of this paper is to evaluate a proposed novel alternative, which applies the internet of thing (IoT) concept, in the observation of wild animal instead of the conventional way which is manpower intensive. The IoT observation system is consisted of the hydrophone laid on the sea floor, camera/IR sensor carried by quadcopter, and land control center. Monte Carlo simulation was developed for getting insight of the interaction between dolphin and IoT observation system. The result showed IoT observation system has a significant effect. The contribution this paper made is to prove that the IoT observation system is far more cost effectively than the manpower intensive boat watching method.